ACTUALIZATION OF NATIONAL EDUCATION STANDARDS ON GRADUATE COMPETENCIES IN JUNIOR HIGH SCHOOL - Sumarsono, Raden Bambang; Rahmawati, Laily Amalia; Enjelica, Lovina Kharisma; Cristinawati, Magdalena Ayu; Mentari, Maula Cahya; Ariyanti, Nova Syafira (International Research-Based Education Journal, 2022)
The purpose of this study was to determine the actualization of National Education Standards on the competence of graduates at the junior high school level. This research uses a qualitative approach, with a case study research design. The principal was a key informant in this study, meanwhile teachers, staff and students were additional informants. The results showed that there were several indicators that were successfully implemented, but there were also some that were not 100% successful. The indicators that are successful to be applied are regarding the assessment of spiritual attitudes that must be achieved by students and the achievement of increasing knowledge in non-academic fields. While the indicators that have not been fully implemented are the assessment of social attitudes that must be achieved by students, the achievement of increased knowledge in the academic field and the assessment of student competency skills.